Historical and Sociological Analysis of the Value World of the Cultural Policy of the Siberian Tatars (The Case Study of the Russian Archive Documents of the 18th – 19th Centuries) - H. Gilfanova, Farida; V. Khvesko, Tamara; D. Raimova, Rosalia; Yu. Pletyago, Tatyana; M. Abysheva, Eugenia (International Journal of Criminology and Sociology, 2022)
The nature of the cultural policy of the Siberian Tatars and its connection with the value world is described for the first time. This material singles out and describes three levels in the development of the anthroponymys value world in the national cultural policy (ancient, middle-aged, and new Turkic). The authors used comparative methods (investigation of archives) and empirical methods, namely, the generalization of the great human experience, which is formed at the levels of cultural policy forming (ancient, middle-aged, and new Turkic). According to the level of religiousness of the ancient Turks, the system of ideas, which is reflected in the needs and desires due to naive mental activity, the authors singled out the ancient model of constructing their cultural policy or the first ancient level of values in the cultural policy of the Siberian Tatars. The anthroponyms system of the Siberian Tatars is an axiological worldview observing objective and subjective evaluative attitudes. The subject in the cultural policy becomes familiar with the value world of name-giving, the system of ideas or ideology appears, which is transformed into a certain stage of development. Cultural policy in the ancient period was created but it is changed in the modern world. The novelty of the study is in the fact that the object category was studied in the cultural policy of Siberian Tatars indefinitely. Our investigation showed interrelation between human being and his experience (object and subject). Our motivation to study the value world of the cultural policy of the Siberian Tatars is supported by the idea that harmony and peace between cultures is possible only in the way of value world and its priorities understanding. New research results complement theoretical generalizations, open up new conceptual opportunities in solving national problems, and make it possible to formulate new strategic goals in our multinational state. They can improve the implementation of cultural policy by social society in goal setting and identification of national cultural values and priorities in the creation on their basis of targeted programs and expenses.